Proyeksi Penduduk Indonesia sampai Tahun 2060 dengan Data Dasar Sensus Penduduk 2020 dan Asumsi Laju Pertumbuhan Penduduk 1,25% - Ricke Aulia Desviandini; Yayat Karyana (Bandung Conference Series: Statistics, 2022)
Abstract. Projections of Indonesia's population in 2010 have been made, including by Sucipto and Tukiran (1992), BPS (2002), Nurwindiagiri (2004), Karyana (2004) and BPS, BAPPENAS and UNFPA (2018). However, because the basic population data and/or assumptions used for the projections are different, the results are also different, and when compared with the results of the 2020 Population Census (SP 2020), none of them are the same. In the period 1971-1980 the population growth rate (LPP) reached 3.2% per year, decreased to 1.97% per year in the period 1980-1990 and to 1.5% per year in the period 1990-2000. However, in the period 2000-2010 it did not decrease, but remained at 1.5% per year. BPS has released the 2020 Population Census Portrait that in the 2010-2020 period there is a population growth rate per year, namely LPP = 1.25% with a population of 270.20 million people. In this thesis, a projection of the Indonesian population until 2060 will be made using the basic data from the 2020 Population Census assuming the LPP population growth rate = 1.25% (BPS, 2020) and using the Mixed Method. The results of the projection of the Indonesian population using the Mixed Method where the population is obtained from the Mathematical Method and the age group section is obtained through the Component Method with basic data from the 2020 Population Census and the assumption of an LPP population growth rate of 1.25% in 2025, 2030, 2035, 2040, 2045, 2050, 2055 and 2060 respectively are 287519166, 305944013, 325549565, 346411482, 368610276, 392231616, 417366663, 444112417 people. Abstrak. Proyeksi penduduk Indonesia tahun 2010 telah dibuat, di antaranya oleh Sucipto dan Tukiran (1992), BPS (2002), Nurwindiagiri (2004), Karyana (2004) dan BPS, BAPPENAS dan UNFPA (2018). Namun karena data dasar penduduk dan atau asumsi yang digunakan untuk proyeksi berbeda, maka hasilnya berbeda pula, dan apabila dibandingkan dengan hasil Sensus Penduduk 2020 (SP 2020) tidak ada yang sama. Pada periode tahun 1971-1980 laju pertumbuhan penduduk (LPP) mencapai 3,2 % per tahun turun menjadi 1,97 % per tahun pada periode 1980-1990 dan menjadi 1,5 % per tahun pada periode 1990-2000. Namun pada periode 2000-2010 tidak turun, tetapi tetap sebesar 1,5 % per tahun. BPS telah merilis Potret Sensus Penduduk 2020 bahwa pada periode tahun 2010-2020 terjadi laju pertumbuhan penduduk per tahun yaitu LPP = 1,25 % dengan jumlah penduduk 270,20 juta orang. Dalam skripsi ini akan dibuat proyeksi penduduk Indonesia sampai tahun 2060 menggunakan data dasar hasil Sensus Penduduk 2020 dengan asumsi laju pertumbuhan penduduk LPP = 1,25 % (BPS, 2020) serta menggunakan Metode Campuran. Hasil proyeksi penduduk Indonesia menggunakan Metode Campuran yang mana jumlah penduduk diperoleh dari Metode Matematik dan bagian kelompok umur didapatkan melalui Metode Komponen dengan data dasar hasil Sensus Penduduk tahun 2020 dan asumsi laju pertumbuhan penduduk LPP sebesar 1,25% pada tahun 2025, 2030, 2035, 2040, 2045, 2050, 2055 dan tahun 2060 berturut-turut adalah 287519166, 305944013, 325549565, 346411482, 368610276, 392231616, 417366663, 444112417 orang.